Strategy for integrated rural development (a case study of a region in Costal Andhra) - Rao, Eadubelli Nagabhushana (Delhi, 1986)
Regional Planning is as important as national planning whichever may be the country, whatever be its geographical character of political philosophy. In Indian setting, it is all the more appropriate to say that rural development means India's development. An attempt has been made in this book for the preparation of a perspective development plan for a region in coastal Andhra, as an important step in the direction of decentralisation of the planning process and adoption of an area approach to development. The very objective in the preparation of such plan is to pool all the available data and knowledge regarding developmental potentialities of the region and place the same at one place for reaby reference to the planning authorities, developmental agencies, students and scholars. This case study could, in fact, serve as a blueprintal for an ideal rural integrated development plan for the country.
Keywords: Rural development